Deepening the conversation on systemic sustainability risks: a social-ecological systems approach - Ahlström, Hanna (Journal of business ethics, 2025)
Narrow views of systemic sustainability risks can result in ecological concerns being neglected, as well as giving rise to unequal distribution and exploitation of natural resources, creating injustice. Given recent advancements in integrating justice with the safe space environmentally, as defined by the planetary boundaries, now is a critical moment for business ethics researchers to deepen the conversation on managing systemic sustainability risks to create a safe and just operating space. We argue that the social-ecological systems approach, that views humans as embedded in and dependent on the natural environment, provides a foundation for business ethics scholars to deepen the conversation. We build on two key dimensions from the social-ecological systems approach, social-ecological connectivity and cross-scale dynamics to develop a framework that illustrates four ways for business ethics scholars to research systemic sustainability risks. We demonstrate the relevance of these dimensions for understanding systemic sustainability risks, discuss their ethical implications, and outline opportunities for future research.